Finding a relationship between the composition and the emulsifying character of asphaltenes through FTICR-MS - Fernando A Rojas-Ruiz; Jorge A Orrego-Ruiz (CT&F Ciencia, Tecnología & Futuro)
ABSTRACT In this work, n-heptane insoluble fractions (asphaltenes) from six crude oils were analyzed by means of Fourier-transform ion cyclotron resonance mass spectrometry (FTICR MS) using both positive Atmospheric Pressure Photo Ionization (+) APPI and negative Electro-Spray Ionization (-) ESI in order to understand their water-oil emulsion stabilization capability on a molecular level basis. Through (+) APPI it was possible to obtain an overview of samples composition. By sorting as nitrogen sulfur and oxygen containing compounds, it was possible to compositionally distinguish the asphaltenes. Through (-) ESI, several differences were also observed by grouping the classes as oxygen (NxOy+NxOySz+Oy+OySz) and non oxygen containing classes (Nx+NxSz). The interactions of these two groups of compounds must be considered in order to understand the water-oil emulsion stability. It implies that the cores where nitrogen and sulfur are part may interact via n-n stacking, while the oxygen containing compounds may interact either via hydrogen bonding or via dipole forces with the aromatic aggregates (highly polarizable), forming potentially surface active aggregates. Thus, the rate between these two families of compounds may determine the surfactant character of asphaltenes at the water-oil interface. Bearing this in mind, an emulsion stability coefficient was proposed based on the relative abundances of some families of compounds detected by (-) ESI-FTICR-MS to explain the crude oils' tendency to form emulsions.